The Predictive and Guidance Value of Signet Ring Cell Histology for Stage II/III Colon Cancer Response to Chemotherapy - Jiang, Huici; Shao, Dongxuan; Zhao, Peiyu; Wu, Yupeng (Frontiers in Oncology, 2021)
Purpose: We aimed to evaluate the predictive and guidance value of signet-ring cell carcinoma for colon cancer response to chemotherapy in stage II/III colon cancer. Methods: Using the Surveillance, Epidemiology and End Results (SEER) database through SEER*Stat software V.8.3.5, eligible patients were recruited from the SEER database. The differences between adenocarcinoma (AD) and SRCC groups in the incidence of patients’ demographic and clinical characteristics were analyzed by Pearson’s chi-squared (χ2) test. Survival was analyzed using the Kaplan–Meier method, and the differences were determined by the log-rank test. Some Cox regression models were built to identify whether a pathological characteristic impacted the prognosis independently and assess hazard ratios (HRs) of different variables with 95% confidence intervals (95% CIs). Results: In stage II AD, it was found that the receipt of chemotherapy had significantly 12.6% decreased risk of cancer-specific mortality (HR = 0.874, 95%CI = 0.825-0.927, P < 0.001). In stage II SRCC, however, the receipt of chemotherapy had significantly 70.00% increased risk of cancer-specific mortality (HR = 1.700, 95%CI = 1.032-2.801, P = 0.037). In stage III AD, it was found that the receipt of chemotherapy had significantly 45.3% decreased risk of cancer-specific mortality (HR = 0.547, 95%CI = 0.530-0.564, P < 0.001). In stage III SRCC, the receipt of chemotherapy had significantly 24.6% decreased risk of cancer-specific mortality (HR = 0.754, 95%CI = 0.632-0.900, P = 0.002). Conclusions: In conclusion, using a large cancer database, we found that the CSS difference between AD and SRCC was not statistically significant in stage II colon cancer and SRCC histology had 14.5% increased risk of cancer-specific mortality compared with the histology of AD in stage III disease. More importantly, we provided the first compelling evidence that chemotherapy should not be treated in stage II SRCC, while stage III SRCC should be treated with chemotherapy.